Performance of Ti-6Al-4V by laser powder bed fusion: powder feedstock and heat treatment considerations - Du, Xi (2024)
Laser powder bed fusion (LPBF) has received significant attention in the past decade due to its capacity to produce complex shaped 3D metallic parts from digital models. Ti and Ti alloys exhibit high potential for medical and aerospace applications due to their low density, high specific strength, good corrosion properties, and good biocompatibility. Among these Ti alloys, Ti-6Al-4V (α+β type) is the most common titanium alloy for various applications. The fabrication of Ti-6Al-4V by LPBF has received extensive attention in recent years. However, the performance of Ti-6Al-4V by LPBF with powder feedstock and heat treatment considerations is not fully understood. This thesis aims at understanding and optimising the performance of Ti-6Al-4V by LPBF considering the role of powder feedstock (including particle size distribution (PSD) and chemical composition) and heat treatment.